Rukyat Qabla Al Ghurub - Ahmad Junaidi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2014)
The unification of the Islamic calendar has been limited in the desire of Muslims. There have been many efforts made in order to realize the ideals of unification. But until now these ideals have not been realized. But we should not despair in finding solutions to realize these ideals for the sake of the establishment of Islamic shi'ar which is rahmatan li al-alamin. One of the latest methods that is expected to be a solution that bridges the unification of the Islamic calendar is Ru'yat Qabl al-Ghurub with Astrophotography technique. This technology-based ru'yat technique can present similarities between data according to calculations and field data.